Analysis of Soil Chemical Properties, Production, and Nitrogen Content of Pakcoy in Various Growth Media and Trichoderma Dosages - Ratih Rahhutami; Aline Sisi Handini; Dwi Astutik; Yeni Yeni (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2023)
The use of compost added by Trichoderma is one of improving the soil's chemical properties and can be used to increase the production of pakcoy plants. The purpose of this study was to determine the effectiveness of compost derived from various types of palm oil waste and the application of Trichoderma on soil chemical properties as well as production and nitrogen content in pakcoy plants. This study used an experimental method with parameters observing plant fresh weight. The research used two factors. The first factor was three types of palm oil waste, midrib leaf, oil palm empty bunches, and solid decanter. The second factor was the dose of Trichoderma, 50 ml, 100 ml, and 150 ml per plant. Planting media derived from solid decanter was able to intensification the production of pakcoy compared to midrib leaf and oil palm empty bunches.